Blocking of Stimulus Control in Children with Autism. - Olaff, Heidi Skorge; Vandbakk, Monica; Holth, Per (Psychological Record, 2022)
The present study aimed to investigate the blocking of stimulus control in three children with autism. We used a go/no-go procedure in a standard blocking paradigm. In Phase 1, we established one of two sounds or colored squares as a discriminative stimulus for touching a tablet screen. In Phase 2, a colored square was added to the sound or a sound was added to the colored square in a stimulus compound. The discrimination training continued as in Phase 1. We subsequently tested discriminative control by each of the single stimuli separately and by the compounds. Finally, after testing with no programmed consequences, we reestablished the original discrimination and replicated the test of stimulus control. The results support previous experiments by demonstrating that the establishment of discriminative control by a second stimulus by adding it to a previously established discriminative stimulus in a compound was blocked by the earlier discrimination training in all three participants. We discuss procedural details that may be critical to avoid the blocking of stimulus control in the applied field, particularly with respect to the acquisition of skills that involve multiple stimuli, such as joint attention, social referencing, and bidirectional naming.